2017
DOI: 10.1111/vox.12501
|View full text |Cite
|
Sign up to set email alerts
|

Life experience of the adult and ageing patient with haemophilia. Practical aspects for psychological support

Abstract: This article discusses, from a psychological perspective, the life experience of the adult and ageing person with haemophilia, including psychological issues, aspects of his personal and social integration, decision-making, communication and other factors that may affect treatment adherence and quality of life. The aim was to provide haematologists and healthcare staff with knowledge and resources to improve communication and support for adult persons with haemophilia, and raise awareness on psychosocial issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The environmental field exhibited a negative trend with age, which may be related to the natural tendency that an individual's physical fitness declines as he/she gets older. In the dimensions of "role-emotional" and "mental health", older patients seemed to score better than younger patients possibly because their rich life experience enabled them to face disease more calmly [26]. 2.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental field exhibited a negative trend with age, which may be related to the natural tendency that an individual's physical fitness declines as he/she gets older. In the dimensions of "role-emotional" and "mental health", older patients seemed to score better than younger patients possibly because their rich life experience enabled them to face disease more calmly [26]. 2.…”
Section: Discussionmentioning
confidence: 99%
“…By studying the prevalence of major depressive disorder and negative behavioral patterns in children and adolescents with hemophilia, those who were randomly selected, it was found that 36% of them had at least a death wish once in the past 6 months (Ghanizadeh & Balich-Jahromi, 2009). Therefore, psychological support and mental health protection are critical for helping children and adolescents with this chronic disease (Torres-Ortuño, Cid-Sabatel, Barbero, & García-Dasí, 2017). Positive psychotherapy is a cognitive psychological strategy and one of the practical approaches that can be effective to obviate psychological problems of hemophilia, considering the age and characteristics of the patients (Thorn, 2017).…”
Section: Plain Language Summarymentioning
confidence: 99%
“…However, the pathophysiology of HA remains incompletely understood, and the pathways are yet to be fully elucidated. HA remains a critical focus of research and study as this debilitating disease negatively impacts quality of life, physical activity, and bone health of the aging PwH population, whose life span is now comparable to that of the normal population 3 , 4 , 14 16 . A gap continues to exist in our ability to detect and impact this sequela at the preclinical or asymptomatic phase when the disease process is early and potentially reversible.…”
Section: Introductionmentioning
confidence: 99%